A new species of Cyrtodactylus (Squamata: Gekkonidae) from northwestern Vietnam - Pham, Anh Van; Le, Minh Duc; Ziegler, Thomas; Nguyen, Truong Quang (Zootaxa, 2019)
We describe a new species of Cyrtodactylus on the basis of seven specimens collected from karst forests of Son La and Dien Bien provinces, Vietnam. Cyrtodactylus taybacensis sp. nov. is distinguished from the remaining Indochinese bent-toed geckos by a combination of the following characters: medium size (SVL up to 97.5 mm); dorsal tubercles in 13–16 irregular rows; ventral scale rows 30–38; ventrolateral folds present without interspersed tubercles; each thigh with 11–13 enlarged femoral scales; femoral pores absent in males and females; precloacal pores 11–13 in males, five or 15 pitted scales in females, in a continuous row; postcloacal tubercles two or three; lamellae under toe IV 16–20; subcaudal scales transversely enlarged; dorsal head with dark brown marking, oval, triangle and arched shape; five brown dorsal bands between limb insertions. In phylogenetic analyses, the new species is recovered as a member of the Cyrtodactylus wayakonei species group, and strongly supported as the sister taxon of C. cf. bichnganae from Son La City in all analyses.